The Determinants of Fertility among Women of Reproductive Age in Nepal - Sharma, Mahendra Prasad (Journal of Development and Administrative Studies, 2016)
This study is conducted on determinants of fertility among women of reproductive age in Nepal. The study takes into account some demographic, socio-cultural, economic and spatial variables. Fertility trends are estimated from the date obtained in the 1996, 2001, and 2006 NDHS with information gathered in the 2011 NDHS. Fertility declined from 4.6 births per woman in the 1996 NFHS to 2.6 births per woman in the 2011 NDHS—a drop of two births per woman in the past 15 years. The decline in fertility is most pronounced in the five years between 2001 and 2006 (a one-child decline). Fertility has declined in every age group over the past 15 years, with largest decline seen among women 25-34 years. But over the past 5 years the largest decline is observed among women 20-24 years. Many factors may have contributed to this quick decline fertility in Nepal, including improved communication and greater access to modern methods of contraception. Extended spousal separations due to migrants seeking work in foreign countries, especially the Gulf countries and other Southeast Asian countries, may be another reason for the fertility decline (NDHS Report 2012). The multivariate analysis is used to show the strength of relationship of fertility with its correlates. It estimates the effect of socio–economic and demographic as well as spatial variables on total Children Ever Born (CEB). This study also attempts to find out variation of fertility among women by using frequency table, rate, ratio, percentage, cross tabulation, correlation and regression analysis and mean CEB. The result shows that when other factors remain unchanged, age of respondents at first birth and educational attainment have strong and significant negative impact on fertility. Similarly son who have died, daughter who have died, parity at sterilization and age at sterilization have strong and significant positive impact on fertility whereas regions, type of place of residence, age at marriage and destination India have weak positive impact on fertility. The Journal of Development and Administrative Studies (JODAS) Vol. 23(1-2), pp. 55-68